Conclusion: old lesson and new directions in food policy - Ahmed, Raisuddin; Haggblade, Steven (International Food Policy Research Institute, 2000)
Two gruesome famines visited Bengal—in 1943 and 1974—on the heels of two great wars. The first descended amid the terrors of World War II, while the second followed in the wake of Bangladesh's brutal war of liberation. Wrenching images from these famines have haunted the nation for two generations— visions of hungry masses, pressed in the crush of extraordinary times, knocking at the doors of the rich, who seldom opened; people dying in hordes, not in the warfields but on apparently peaceful and idle compounds, on roadsides destroyed by war, on barren rice fields and in empty markets. Vivid memories of these famines linger in the minds of the elders who have steered economic policies in postwar periods and peacetime. Haunted by these ghosts from the past, policymakers have persistently erred on the side of intervention in food markets through direct public distribution of foodgrains and tight market regulation.